Minimum wage analysis using a pre-committed research design: Evidence through 2017 - Michael R. Strain; Jeffrey Clemens (American Enterprise Institute (AEI), 2019)
This paper presents results from the third year of a multiyear, pre-committed research design for analyzing recent minimum wage changes.
Keywords: A; 330; Minimum Wage; employment; household income